A Mini-Review On Emerging Trends and Recent Advances in Analytical Methods for Covid-19: Analytical Chemistry Perspective (British Journal of Multidisciplinary and Advanced Studies, 2023)
In recent times SARS-CoV-2 pandemic, public health experts have slated testing, tracking infected people, as well as tracing their contacts as an efficient method to reduce the viral spread. Numerous diagnostic approaches are reported for detecting the coronavirus in public health, clinical and research laboratories. Most tests detect the infection directly by detecting the viral RNA while other test may indirectly detect the host antibodies in the course of detecting the infection. A diagnostic test during the pandemic should aid in making proper clinical decision within a short time frame. In this review, we describe the various techniques involved in sample collection from nasal, throat and sputum specimens, standard and developed methods for diagnosis of covid 19 such as the polymerase chain reaction (RT-PCR), CRISPR-based assays and Serological and immunological assays.  General information on selected electroactive antiviral Covid-19 drugs have been highlighted including: Favipiravir (FAV), Remdesivir (REM), Lopinavir + Ritonavir (LOP + RIT), Hydroxychloroquine (HCQ) and Chloroquine (CQ), Ribavirin (RIB) and Sofosbuvir. This review presents the major standard, commercial and designed methods for detecting SARS-CoV-2 and their analytical performance. Also, chromatographic techniques have been highlighted as a rapid examination for SARS-CoV-2 identification, and some recent advances and emerging trends in analytical methods for covid-19 diagnosis have been addressed.